Determination of Institutional Factors on The Effectiveness of The Pesiar Program in Promoting Universal Health Coverage in Semarang City - Upik Handayani; Aris Toening W; Permadi Mulajaya (International Journal of Health and Medicine, 2026)
The PESIAR Program (Petakan, Sisir, Advokasi, dan Registrasi Map, Screen, Advocate, and Register) is an operational instrument of BPJS Kesehatan designed to accelerate the achievement of Universal Health Coverage (UHC) by increasing National Health Insurance (JKN) membership at the local level. However, the effectiveness of this program’s implementation is strongly determined by the institutional capacity and configuration that support it. This article aims to reposition institutional determination not only as a factor influencing program effectiveness, but as a model of administrative governance in achieving UHC. The study uses a mixed methods approach with a sequential explanatory design. Quantitative data were obtained through a survey of PESIAR Agents in Semarang City, while qualitative data were collected through open-ended questionnaires and interviews. The results show a strong, positive relationship between institutional determination and the effectiveness of the PESIAR Program. Qualitative findings further clarify that issues of program effectiveness largely originate from institutional capacity, the quality of cross-sector coordination, and the role of PESIAR Agents as field implementers. This study concludes that institutional determination deserves to be positioned as an administrative governance model for the PESIAR Program in promoting the achievement of UHC at the local level.